Peltier Elements-based Human Brain Hypothermia Treatment - Rabab Talib Abdullah; Sadik Kamel Gharghan; Ahmed J. Abid (Journal of Techniques)
Cooling and hypothermia of the brain is an important and effective way to save the lives of many patients suffering from diseases such as strokes, epilepsy, incurable diseases, and others due to general accidents. Brain cells are also weak and sensitive to changes and fluctuations in human temperature. In this work, a hypothermia device was designed and practically implemented to reduce the brain and body temperature. It mainly consists of temperature sensors for measuring water and patient temperature, a Helmet made of plastic tubes with a thermal coefficient suitable for absorbing heat, cold water is circulated inside the tubes to cool the head, and the cooling is done through Peltier elements in the device. The Arduino microcontroller controls the system. The experimental results showed a decreasing in brain temperature to 36.5 °C within a cooling time of 12 minutes. The effectiveness of the proposed system was also validated by comparing the findings with the previous system in terms of temperature and cooling time.